Apelacja obrońcy węzła małżeńskiego w procesie zwyczajnym o stwierdzenie nieważności małżeństwa - Kamiński, Rafał (Ius Matrimoniale, 2018)
The right to appeal resulting from natural justice serves to guarantee a fair judgment. Also after the reform of the marriage process carried out by Pope Francis in 2015, the appeal remains the primary appeal, which can be used by the private and public parties involved in the case. This article discusses the norms and principles that should be maintained when an appeal in the ordinary trial for nullity of marriage is made by the defender of the bond. His public office not only authorizes him, but in certain conditions also obliges him to use the institution of appeal. After presenting the legal basis of the law and the duty of the defender of the bond to appeal, the procedure of its submission, the applicable time limits and the nature of the justification that must take place after filing the appeal are discussed. In the last part, the reflection concerns problematic issues associated with the application of the new norm contained in can. 1680 KPK standards, the judges’ attitude towards the application and the court costs incurred in connection with the submission of an appeal.